Analysis of relative age effect in muscular strength of adolescent swimmers - Atar, Ö.; Özen, G.; Koç, H. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2019)
Purpose: The aim of this study is to analyse the effect of relative age in anthropometric measurements, muscular strength of adolescent swimmers. Material and Methods: The study sample was composed of 40 volunteers adolescent well-trained swimmers. Participants were grouped as swimmers born in the first quarter (January, February and March) and in the last quarter (October, November and December) of the same year. Anthropometric measurements were taken from each participant, and body mass index of participants were calculated. To determine performance parameters, handgrip, back and leg strength tests were performed on participants. The level of statistical significance was set at p < .05. Results: Statistical analysis showed that there were statistically significant differences in the body height and BMI ( p < .05 ), but body weight differences were not statistically significant between swimmers who are born first and last quarter of the same year ( p > .05 ). There were significant differences in the means of absolute leg and handgrip strength between relative age groups. There were statistically significant differences in the means of relative back, leg and handgrip strength between groups ( p < .05 ). All mean relative strength values of participants significantly differed in favour of the group born in the first quarter of the year. Conclusion: As a result of this study, it is determined that relative age has an effect on the measured anthropometric and muscular strength parameters of adolescent well-trained swimmers. The findings of this study revealed that relative age is an important factor to be considered in swimming performance in adolescent swimmers.